2016
DOI: 10.1177/0269881116628430
|View full text |Cite
|
Sign up to set email alerts
|

Decreased mental time travel to the past correlates with default-mode network disintegration under lysergic acid diethylamide

Abstract: This paper reports on the effects of LSD on mental time travel during spontaneous mentation. Twenty healthy volunteers participated in a placebo-controlled crossover study, incorporating intravenous administration of LSD (75 μg) and placebo (saline) prior to functional magnetic resonance imaging (fMRI). Six independent, blind judges analysed mentation reports acquired during structured interviews performed shortly after the functional magnetic resonance imaging (fMRI) scans (approximately 2.5 h post-administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 81 publications
4
69
0
Order By: Relevance
“…Clinical experimental research with LSD has recently seen a resurgence (Carhart-Harris et al 2016b; Carhart-Harris et al 2015; Carhart-Harris et al 2016c; Dolder et al 2015b; Dolder et al 2016; Kaelen et al 2015; Kaelen et al 2016; Lebedev et al 2016; Roseman et al 2016; Schmid et al 2015; Speth et al 2016; Strajhar et al 2016; Tagliazucchi et al 2016; Terhune et al 2016). An increasing amount of data has been generated on the effects of LSD (75 μg) on various neuronal correlates of brain activation (Carhart-Harris et al 2016c; Kaelen et al 2016; Lebedev et al 2016; Roseman et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical experimental research with LSD has recently seen a resurgence (Carhart-Harris et al 2016b; Carhart-Harris et al 2015; Carhart-Harris et al 2016c; Dolder et al 2015b; Dolder et al 2016; Kaelen et al 2015; Kaelen et al 2016; Lebedev et al 2016; Roseman et al 2016; Schmid et al 2015; Speth et al 2016; Strajhar et al 2016; Tagliazucchi et al 2016; Terhune et al 2016). An increasing amount of data has been generated on the effects of LSD (75 μg) on various neuronal correlates of brain activation (Carhart-Harris et al 2016c; Kaelen et al 2016; Lebedev et al 2016; Roseman et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The 5D-ASC scale has been used in all of the recent experimental studies with LSD (Carhart-Harris et al 2016b; Carhart-Harris et al 2016c; Schmid et al 2015; Tagliazucchi et al 2016) and with many other psychedelics, providing an opportunity to compare findings between studies and across substances and research groups. Thus, the present study assessed LSD dose- and plasma concentration-response functions using the 5D-ASC scale in 40 subjects (Dolder et al 2015b; Dolder et al 2016; Schmid et al 2015), thus allowing comparisons with other studies that used the 5D-ASC scale but did not determine plasma LSD concentrations (Carhart-Harris et al 2016b; Carhart-Harris et al 2016c; Kaelen et al 2016; Lebedev et al 2016; Roseman et al 2016; Speth et al 2016; Tagliazucchi et al 2016; Terhune et al 2016). A third goal of the present study was to assess associations across subjects between the peak and total plasma exposure to LSD and its effects on 5D-ASC scale scores (Studerus et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Altered states of consciousness induced by methods as varied as sensory deprivation, shamanic drumming, trance, meditation, endurance running, hallucinogen consumption, and even epileptic seizures produce shared cognitive and behavioral effects, including hallucinations, out-of-body experiences, ego dissolution, enhanced imagery, and a distorted sense of time (see Castillo 1990;Danielson et al 2011;Dietrich 2003;Forgays & Forgays 1992;Hayashi et al 1992;Kjellgren et al 2003;Mason & Brady 2009;Speth et al 2016;Suedfeld 1980;Suedfeld & Eich 1995;Vaitl et al 2005;Zuckerman & Cohen 1964). These shared effects are not likely to be coincidental; rather, it is likely that ASC share certain neurophysiological features that correspond to these cognitive and behavioral effects.…”
Section: Shadab Tabatabaeian and Carolyn Dicey Jenningsmentioning
confidence: 99%
“…The DMN is activated during self-referential processes, such as autobiographical memory retrieval (Boly et al 2008;Buckner et al 2008;Raichle et al 2001). Studies using fMRI have indicated that, during ASC induced by various methodsincluding focused meditation (Brewer et al 2011), hallucinogen consumption (Carhart- Palhano-Fontes et al 2015;Tagliazucchi et al 2016;Speth et al 2016), and epileptic seizures (Danielson et al 2011)the activation of the DMN decreases, giving rise to ego dissolution. These studies also reveal that, during ASC, regardless of induction method, high functional connectivity is exhibited between three interacting brain networks: default mode, frontoparietal control, and salience (see Brewer et al 2011;Hasenkamp et al 2012;Hove et al 2016;Tagliazucchi et al 2016).…”
Section: Shadab Tabatabaeian and Carolyn Dicey Jenningsmentioning
confidence: 99%
“…Extreme sensate focus has the potential to crowd-out ruminative processes (Kerr, Sacchet, Lazar, Moore, & Jones, 2013; Meston, Hull, Levin, & Sipski, 2004; Michalak, Hölz, & Teismann, 2011) and even prevent the recruitment of neural resources for other mental simulations (Barsalou, 2009; Pezzulo et al, 2011; Simmons et al, 2005), including the kinds of imaginings required for modeling the self in the past, future, or other counterfactual situations (Smallwood et al, 2012; Speth et al, 2016). Such an experience of sensate focusing and altered self-processing may be most appropriately referred to as a kind of trance state.…”
Section: The Neurophenomenology Of Sexual Trancementioning
confidence: 99%